2008
DOI: 10.1111/j.1365-2214.2008.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ personality and parenting stress in families of children with spina bifida

Abstract: Mobility, bladder and bowel dysfunctions in school-aged children with SB represent ongoing stressors for parents. Parents' intrapersonal resources of positive affectivity, however, are more important determinants of parental adjustment to SB than the child's physical dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 24 publications
(55 reference statements)
1
57
1
Order By: Relevance
“…As the mother is the primary caregiver in many instances, she is continually exposed to these demands on her time and emotional well-being. 4 In our study, 56.8% of spina bifida children required CIC and the majority had this performed by the mother. Even though 45.7% were still wet, the results suggest that the need for CIC itself rather than the incontinence contributed to maternal perception that the child is 'difficult' and that her parental role is stressful.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…As the mother is the primary caregiver in many instances, she is continually exposed to these demands on her time and emotional well-being. 4 In our study, 56.8% of spina bifida children required CIC and the majority had this performed by the mother. Even though 45.7% were still wet, the results suggest that the need for CIC itself rather than the incontinence contributed to maternal perception that the child is 'difficult' and that her parental role is stressful.…”
Section: Discussionmentioning
confidence: 53%
“…Marital status has been consistently linked to personal well-being, even in adults without handicapped children, 19 while the presence of a significant adult companion improved maternal self-reports of wellbeing, satisfaction and competence in mothers of children with spina bifida. 20 Vermais et al 4 too showed that the presence of a partner correlated with fewer psychological symptoms in parents of children with spina bifida. Thus, it is possible that the loneliness, lack of physical and emotional support, and lack of respite from the care-giving needs of the spina bifida child that accompanies the absence of adult companionship in a marriage have given rise to the increased stress scores in our single-parent families.…”
Section: Single-parent Statusmentioning
confidence: 99%
See 3 more Smart Citations